Stability for the Calderón's problem for a class of anisotropic conductivities via an ad hoc misfit functional. (17th November 2021) - Foschiatti, Sonia; Gaburro, Romina; Sincich, Eva
Abstract: We address the stability issue in Calderón's problem for a special class of anisotropic conductivities of the form σ = γA in a Lipschitz domain Ω ⊂ R n, n ⩾ 3, where A is a known Lipschitz continuous matrix-valued function and γ is the unknown piecewise affine scalar function on a given partition of Ω. We define an ad hoc misfit functional encoding our data and establish stability estimates for this class of anisotropic conductivity in terms of both the misfit functional and the more commonly used local Dirichlet-to-Neumann map.